Hardware and software support for decision-making in the management of - Фабричев, В. А.; Гатилов, А. В. (Problems of Informatization and Control, 2004)
The model of interaction of divisions on resource management of bank represented, levels of organization of an information-analytical tree of bank are defined, classes of accepted solutions are defined, tasks and requirements to a decision support system on resource management of bank are formulated, further ways of system’s evolution are proposed